Enhancing patient education and engagement through digital intelligence tools in dermatology - Herrick, Grace; Frasier, Kelly; Li, Vivian; Fritts, Haily; Woolhiser, Emily; Vinagolu-Baur, Julia (International Journal of Research in Dermatology, 2024)
This comprehensive digital health review examines the expanding landscape of digital intelligence tools within dermatology, specifically examining the innovative role of AI-powered applications aimed at educating and engaging patients in managing their skin health. Drawing upon a wide array of existing research, this review scrutinizes the evolution and impact of various digital tools. These include interactive apps that leverage AI algorithms to deliver tailored skincare guidance, considering factors such as skin type, concerns, and environmental factors. Additionally, the review explores the emerging use of immersive virtual reality experiences to deepen patients’ understanding of skin conditions, offering vivid simulations and educational content. These innovative approaches showcase significant promise in not only improving patient outcomes but also fostering greater treatment adherence and overall satisfaction with dermatological care. Looking ahead, future research should prioritize fine-tuning AI algorithms to further personalize patient recommendations, exploring the integration of wearable technology for real-time monitoring, and conducting longitudinal studies to evaluate the sustained effectiveness and scalability of digital intelligence tools in promoting patient education and engagement. Moreover, innovative strategies such as gamification techniques and social support platforms hold considerable potential for enhancing patient empowerment and involvement in managing their skin health. Leveraging digital intelligence tools will eventually redefine the landscape of dermatological care, empowering patients and optimizing treatment outcomes through enhanced education and engagement.